Soil organic carbon under various land uses in alfisols of Eastern India - KUMAR, AMARJEET; PADBHUSHAN, RAJEEV; SINGH, YANENDRA KUMAR; KOHLI, ANSHUMAN; GHOSH, MAINAK (The Indian Journal of Agricultural Sciences, 2021)
Majority land use changes from the natural forests to commercial agricultural lands, orchards and grazing lands have occurred due to deforestation and land degradation. Soil organic carbon (SOC) is considered as one of the important soil quality parameters for sustainable land management. The present study was formulated to understand the effects of land use changes from forest land to cultivated lands, orchards and grazing lands on carbon pools and carbon stocks in subtropical alfisol ecosystem of Banka district of Eastern India 2015-16. Results showed that soil organic carbon (SOC) in the cultivated land was declined by 47%, 23% and 13%, respectively as compared with the forests, orchards and grazing lands of the soil depth 0-15 cm and 37%, 12% and 12%, respectively in the same order of the soil depth 15-30 cm. The loss of carbon stock in the cultivated soil in the top 30 cm was 14%, and in orchard and grazing land was almost similar while keeping forest soils as a reference. In surface soil, carbon management index (CMI) values for grazing, cultivated and orchards were 93, 83 and 95, respectively, whereas in subsurface soil CMI values for grazing, cultivated and orchards were 95, 92 and 96, respectively as compared to forest land. Overall, SOC content was declined on conversion of forest land to cultivated land in the region. This is alarming situation and requires managing cultivated soil properly otherwise soil productivity will deteriorate and in turn will affect crop productivity in the region.